Hydrotransport 6 - 249421 Stephens, Herbert Simon; International Conference on the Hydraulic Transport of Solids in Pipes (6th : 1979 : Canterbury; Gittins, Lavinia (Cranfield : BHRA Fluid Engineering, 1979)
20